2015
DOI: 10.1071/wr14164
|View full text |Cite
|
Sign up to set email alerts
|

What drives cat-owner behaviour? First steps towards limiting domestic-cat impacts on native wildlife

Abstract: Context Cats can have substantial negative impacts on native wildlife. To harness the collective conservation impact of owners keeping cats inside, advocacy campaigns need to be based on empirical evidence regarding potential drivers to change cat-owner behaviour. Aims We assessed the degree to which different socio-psychological factors (attitudes, subjective norms, and perceived behavioural control), past cat owner behaviour, demographics and group membership explained intentions of zoo visitors to bring cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 40 publications
3
49
0
2
Order By: Relevance
“…Specific to our context and problem, we modified McKenzie‐Mohr's () formula by adding a fourth variable: veterinarians' ranking of the impact of the behavior on cat welfare, because we were interested in delivering our future advocacy campaign from veterinary clinics. Veterinarians have a strong expert and normative influence over cat owners, particularly with respect to animal welfare (Harrod et al, ; MacDonald et al, ). Veterinarians have been successful advocates in previous owner‐behavior change initiatives (e.g., Byers et al, for improving owner and dog health) and could also be an important influence on cat owners.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific to our context and problem, we modified McKenzie‐Mohr's () formula by adding a fourth variable: veterinarians' ranking of the impact of the behavior on cat welfare, because we were interested in delivering our future advocacy campaign from veterinary clinics. Veterinarians have a strong expert and normative influence over cat owners, particularly with respect to animal welfare (Harrod et al, ; MacDonald et al, ). Veterinarians have been successful advocates in previous owner‐behavior change initiatives (e.g., Byers et al, for improving owner and dog health) and could also be an important influence on cat owners.…”
Section: Methodsmentioning
confidence: 99%
“…Cat inside at night Cat brought inside from dusk until dawn every night Reduce home range; cat home range correlated to predation (Robertson, 1998) (Hall et al, 2016b) influence over cat owners, particularly with respect to animal welfare (Harrod et al, 2016;MacDonald et al, 2015). Veterinarians have been successful advocates in previous ownerbehavior change initiatives (e.g., Byers et al, 2014 for improving owner and dog health) and could also be an important influence on cat owners.…”
Section: Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Given that cat populations and behaviour are influenced, directly and indirectly, by human behaviour, integrating cat owners as research participants will be vital to improving our understanding of human-cat-environment relations, and to the development and application of effective, sustainable solutions to the environmental challenges created by the global abundance of people and their cats. Recent research has provided important insights into drivers of cat owner behaviour [28,[30][31][32] and the effectiveness of different techniques for communication and behaviour change [33][34][35]. However, beyond behaviour change initiatives, good-faith engagement between cat owners and advocates, wildlife conservationists, and scientists will be vital to understanding differing perspectives, concerns, and priorities, and to constructively deliberating on human responsibilities to and for domestic cats.…”
Section: Outstanding Questionsmentioning
confidence: 99%
“…Recent research has suggested that advocacy campaigns for cat containment that focus on the benefits to cat welfare, rather than wildlife conservation, may be more successful (MacDonald et al 2015;Hall et al 2016) and that a better understanding by cat owners of the risks encountered by free-ranging cats may result in behaviour change (Gramza et al 2016). Integrating social science with ecological studies is particularly useful, and can be achieved well by using citizen-science methodologies.…”
Section: Social Studiesmentioning
confidence: 99%